EFEKTIVITAS CAPACITY BUILDING DALAM MENINGKATKAN KINERJA PEGAWAI PPPPTK PENJAS DAN BK - ENDANG SETYORINI (TEACHER : Jurnal Inovasi Karya Ilmiah Guru, 2022)
Concern and quality of Human Resources (HR) is a factor that greatly influences the development of an institution/institution. Therefore, human resource capacity building is an absolute must. Capacity building is an activity to increase knowledge, skills, attitudes, and behavior of human resources. Capacity building activities are able to build communication, self-motivation, creativity, problem solving skills (problem solving) and decision making (decision making) quickly and accurately, as well as leadership skills (leadership). The purpose of this study was to see the effectiveness of capacity building in improving the performance of PPPTK Penjas and BK employees based on the employee's perspective. The methodology used in this research is descriptive qualitative. The instrument used was in the form of a questionnaire given to PNS PPPTK Penjas and BK employees. The results of the study show that capacity building is effective in improving employee performance because capacity building is ultimately able to increase self-confidence in working and relating to others, increasing work motivation, increasing efforts to achieve work performance, increasing cooperation in work teams, improving communication with colleagues, and improving excellent service to the public, as well as increasing the contribution of human resources to the performance of institutions/institutions. ABSTRAKKepedulian dan kualitas Sumber Daya Manusia (SDM) merupakan faktor yang sangat mempengaruhi berkembang tidaknya suatu institusi/lembaga. Oleh karena itu pengembangan kapasitas (capacity building) SDM menjadi hal yang mutlak dilakukan. Capacity building merupakan kegiatan peningkatan pengetahuan (knowledge), keterampilan (skills), sikap (attitude), dan perilaku (behaviour) SDM. Kegiatan capacity building mampu membangun komunikasi, motivasi diri, kreativitas, keterampilan memecahkan masalah (problem solving) dan pengambilan keputusan (decision making) secara cepat dan tepat, serta kemampuan dalam kepemimpinan (leadership). Tujuan dari penelitian ini adalah untuk melihat efektivitas capacity building dalam meningkatkan kinerja pegawai PPPPTK Penjas dan BK berdasarkan perspektif pegawai. Metodologi yang digunakan dalam penelitian ini adalah deskriptif kualitatif. Instrumen yang digunakan berupa angket yang diberikan kepada Pegawai PNS PPPPTK Penjas dan BK. Hasil penelitian memperlihatkan bahwa capacity building efektif meningkatkan kinerja pegawai karena capacity building pada akhirnya mampu meningkatkan rasa percaya diri dalam bekerja dan berhubungan dengan orang lain, meningkatkan motivasi kerja, meningkatkan upaya meraih prestasi kerja, meningkatkan kerjasama dalam tim kerja, memperbaiki komunikasi dengan rekan kerja, dan meningkatkaan pelayanan prima kepada publik, serta meningkatkan kontribusi SDM pada kinerja lembaga/institusi.